Effect of Hyaluronic Acid Iontophoresis on Healing of Chronic Venous Ulcer - Heba Abdelsamad Ramadan, Wafaa H. Borhan, Ashraf Elsebaie Mohamed, Hussein Gamal Hussein Mogahed, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The purpose of the study is to evaluate the effect of hyaluronic acid iontophoresis on healing of chronic venous ulcer. Methods: Forty patients of both genders suffering from chronic venous ulcer in area below the knee and above the ankle with area (5-20 cm2) with less than 50% necrotic tissue participated in this study. Their ages ranged from (45 to 60) years. They were selected from Vascular Surgery Department, Al Ahrar Teaching Hospital between June 2022 and January 2023. Patients were divided randomly into 2 equal groups; each one had 20 patients. Group (A) received Hyaluronic acid iontophoresis 1 session per day, 3 sessions per week, for 4 weeks, and follow up 4 weeks after the end of the treatment. In addition to conventional, medical treatment and traditional care. Group (B) received conventional medical treatment and traditional care (ulcer cleansing, debridement, dressing, compression, medication, exercise). Measurements were done by photographic digital camera for wound Surface area (WSA) and wound volume using saline injection into a wound cavity before treatment and after 4 weeks of treatment. Results: The findings of this study indicated significant decrease in WSA and wound volume after treatment in all groups A, B (p<0.001) at day 60 post treatment. There was significant decrease in ulcer surface area and ulcer volume at day 60 post treatment of study group (group A) compared with that of control group (group B) (p = 0.001).Conclusion: Hyaluronic acid iontophoresis for 6 weeks is an effective and safe adjuvant therapy in treatment of unhealed venous ulcers through accelerating wound healing, reducing Wound Surface Area (WSA) and wound volume. Keywords: Hyaluronic Acid, iontophoresis, Chronic Venous leg ulcers, Wound Healing.